11.COMBINING STRAIN ELASTOGRAPHY FINDINGS WITH ULTRASOUND BIRADS SYSTEM TO DISCRIMINATE BETWEEN BENIGN AND MALIGNANT SOLID BREAST MASSES (Iraqi Journal of Medical Sciences, 2018)
Background: Elastography has been attracting attention as a new non-invasive diagnostic tool with the potential to improve breast masses characterization.Objective: To assess the value of incorporating strain elastography into the ultrasound Breast Imaging Reporting and Data System (BIRADS) System to differentiate benign from malignant breast masses.Methods: Fifty-six women with 61 solid breast masses were enrolled in this study. Ultrasound was performed and the mass was given an US BIRADS category. Elastographic examination was performed and each lesion was assigned an Elasticity Score (ES) according to the Tsukuba scoring system. Strain Ratios (SRs) were calculated from a tumor adjusted Region of Interest (ROI) and a reference ROI in the fatty tissue. The US BIRADS was modified according to the elasticity criteria. Sensitivity, specificity, area under the curve (AUC) and cutoff values were calculated for US BIRADS, ES, SR and the modified BIRADS method using (ROC) curve analysis. Results: The final results were based on 61 masses, 25 benign and 36 malignant. The sensitivity and specificity were respectively (97% and 80%) for US BIRADS, (86.1% and 84%) for ES, (94.44% and 84%) for SR, and (97% and 84%) for the modified BIRADS. Conclusion: Combining elastography with conventional ultrasound yielded better diagnostic performance with improved specificity.Keywords: Elastography, breast masses, elasticity, strain ratio, modified BIRADSCitation: Tawfeeq RHA, Khalel EA, Al-Waely NKN. Combining strain elastography findings with ultrasound BIRADS system to discriminate between benign and malignant solid breast masses. Iraqi JMS. 2018; Vol. 16(1): 74-83. doi: 10.22578/IJMS.16.1.11
Keywords: Elastography; breast masses; elasticity; strain ratio; modified BIRADS